2016
DOI: 10.1016/j.cjtee.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between trauma-induced coagulopathy and progressive hemorrhagic injury in patients with traumatic brain injury

Abstract: Progressive hemorrhagic injury (PHI) can be divided into coagulopathy-related PHI and normal coagulation PHI. Coagulation disorders after traumatic brain injuries can be included in trauma-induced coagulopathy (TIC). Some studies showed that TIC is associated with PHI and increases the rates of disability and mortality. In this review, we discussed some mechanisms in TIC, which is of great importance in the development of PHI, including tissue factor (TF) hypothesis, protein C pathway and thrombocytopenia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
7
0
4
Order By: Relevance
“…Clinical risk factors or predictors studies showed that TIC closely related with PHI and PTCI (Tian et al, 2010;Yuan et al, 2012;Chen et al, 2013;Maegele, 2013;Yang et al, 2014;de Oliveira Manoel et al, 2015;Liu and Tian, 2016), which implied that TBI can break the dynamic balance between procoagulant and fibrinolytic systems to promote coagulation disorder, and it might be the important contributor to the initiation of pathological cascade secondary injury processes, including progressive hemorrhagic and ischemic brain injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical risk factors or predictors studies showed that TIC closely related with PHI and PTCI (Tian et al, 2010;Yuan et al, 2012;Chen et al, 2013;Maegele, 2013;Yang et al, 2014;de Oliveira Manoel et al, 2015;Liu and Tian, 2016), which implied that TBI can break the dynamic balance between procoagulant and fibrinolytic systems to promote coagulation disorder, and it might be the important contributor to the initiation of pathological cascade secondary injury processes, including progressive hemorrhagic and ischemic brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive hemorrhagic injury (PHI), one of the most important and devastating complications after initial brain injury, is reported to be significantly associated with trauma-induced coagulopathy (TIC) (Maegele, 2013;Yang et al, 2014;de Oliveira Manoel et al, 2015). Our previous studies demonstrated that the risk of PHI after TBI can be predicted by some parameters of coagulopathy, including high D-dimer level, prolonged prothrombin time (PT), or low platelet count (Tian et al, 2010;Yuan et al, 2012;Liu and Tian, 2016). Post-traumatic cerebral infarction (PTCI) is also a severe secondary brain injury after TBI, with a reported incidence ranging from 1.9 to 18.8% (Server et al, 2001;Marino et al, 2006;Tawil et al, 2008;Tian et al, 2008;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Coagulopathy was diagnosed based on findings of prothrombin time (PT), international normalized ratio (INR), or activated partial thromboplastin time (aPTT) above the range for age as defined by standardized institutional laboratory values for coagulation markers in the pediatric population or platelet counts of 100 × 10 3 /µl or less 18 (Table 1).…”
Section: Methods and Measurementsmentioning
confidence: 99%
“…1,28 Various mechanisms leading to hypocoagulability have been proposed to explain the pathogenesis of primary coagulopathy in isolated TBI, including hypothesized tissue factor release, protein C pathway activation, thrombocytopenia, and platelet dysfunction. 7,9,18,25,32,33 The incidence of and mechanisms resulting in acute coagulopathy differ between coagulopathies associated with penetrating injuries versus blunt head injuries. 10,28…”
mentioning
confidence: 99%
“…nungsstörung [18]. Multiple Makromoleküle wie der Tissue Factor (TF), Tissue Plasminogen Activator (tPA), Urokinase Plasminogen Activator (uPA) und Protein C scheinen an der Entstehung beteiligt zu sein [20,23,24]. Auch Mikropartikel wie Phospholipide (sog.…”
Section: Sht-bedingte Koagulopathieunclassified